Optimizing the implementation of the Saber post-quantum cryptography scheme with a hybrid architecture - Sabyrzhan Atanov; Khuralay Moldamurat; Luigi La Spada; Makhabbat Bakyt; Adil Maidanov (Bulletin of Electrical Engineering and Informatics, 2026)
This paper presents a hardware–software hybrid implementation of the Saber key encapsulation mechanism (KEM) on a Terasic DE10-Nano board, which combines an ARM Cortex-A9 processor and an Intel Cyclone V field programmable gate array (FPGA). By offloading computationally intensive polynomial multiplication to a dedicated FPGA module, the hybrid design significantly reduces execution time. Experimental results show that compared to a software-only approach, the hybrid design decreases execution time by 40% for key generation, 35% for encapsulation, and 50% for decapsulation. The consistent performance gains were confirmed across the LightSaber, Saber, and FireSaber parameter sets, demonstrating that CPU-FPGA co-design offers significant efficiency improvements for post quantum cryptography (PQC), especially on platforms with limited resources.